(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To characterize children and adults with intestinal stoma in relation to sociodemographic and clinical aspects of the State Reference Center of Bahia. Method: This is a cross-sectional descriptive research, with a quantitative approach and a convenience sample of 43 patients that met the inclusion criteria. The data were collected through an interview and evaluation of the stoma and skin, around and analyzed by descriptive statistics, with frequency and percentage distribution. Results: There was a predominance of males, aged between 40 and 59 years old, unmarried, with incomplete elementary education, family income of a minimum wage, having colorectal cancer and firearm trauma as responsible for the stoma. It emphasized the occurrence of temporary descending colostomy, use of a drainable device, a single piece, with a cut-off, with a cut greater than the diameter of the stoma, presence of dermatitis. Stomatal hygiene and device switching were performed independently. Conclusion: The results of the study indicated a need to reassess the strategies used in specialized care, with emphasis on educational actions aimed at self-care and greater participation of the user in the program, aiming at their rehabilitation and improvement in quality of life.